Maximizing the Use of Edmodo in Writing with the Aids of Online Collaborative Learning Tools - Noor Azlinda, Zainal Abidin; Zuraina, Ali (2016)
Technology plays an important role in effective teaching and learning. It also changes students’ way of working and completing work assigned. In this study, Edmodo is used to examine tertiary level students’ writing skills. A pre-test and post-test are used to measure students’ scores in both of the tests. Besides that, the online collaborative learning tools i.e Prezi, Padlet and YouTube are utilized as supplementary tools to facilitate the students in writing their essays. Students’ comments on these collaborative learning tools are also analyzed. Findings from the study revealed that there are significant differences in the pre and post-tests. It is also found that the use of the collaborative learning tools do help the students in understanding better. This study makes a significant contribution to research on the use of Edmodo by demonstrating its use in essay writing.